Vaginal Microbiota of Adolescent Girls Prior to the Onset of Menarche Resemble Those of Reproductive-Age Women - Roxana J. Hickey (American Society for Microbiology, 2015)
ABSTRACT Puberty is an important developmental stage wherein hormonal shifts mediate the physical and physiological changes that lead to menarche, but until now, the bacterial composition of vaginal microbiota during this period has been poorly characterized. We performed a prospective longitudinal study of perimenarcheal girls to gain insight into the timing and sequence of changes that occur in the vaginal and vulvar microbiota during puberty. The study enrolled 31 healthy, premenarcheal girls between the ages of 10 and 12 years and collected vaginal and vulvar swabs quarterly for up to 3 years. Bacterial composition was characterized by Roche 454 pyrosequencing and classification of regions V1 to V3 of 16S rRNA genes. Contrary to expectations, lactic acid bacteria, primarily Lactobacillus spp., were dominant in the microbiota of most girls well before the onset of menarche in the early to middle stages of puberty. Gardnerella vaginalis was detected at appreciable levels in approximately one-third of subjects, a notable finding considering that this organism is commonly associated with bacterial vaginosis in adults. Vulvar microbiota closely resembled vaginal microbiota but often exhibited additional taxa typically associated with skin microbiota. Our findings suggest that the vaginal microbiota of girls begin to resemble those of adults well before the onset of menarche. IMPORTANCE This study addresses longitudinal changes in vaginal and vulvar microbial communities prior to and immediately following menarche. The research is significant because microbial ecology of the vagina is an integral aspect of health, including resistance to infections. The physiologic changes of puberty and initiation of cyclic menstruation are likely to have profound effects on vaginal microbiota, but almost nothing is known about changes that normally occur during this time. Our understanding has been especially hampered by the lack of thorough characterization of microbial communities using techniques that do not rely on the cultivation of fastidious bacteria, as well as a dearth of studies on girls in the early to middle stages of puberty. This study improves our understanding of the normal development of vaginal microbiota during puberty and onset of menarche and may better inform clinical approaches to vulvovaginal care of adolescent girls.